Allyn and Bacon quick guide to writing - Ramage, John D. (Allyn and Bacon, 1996)
Solidly grounded in current theory and research, yet eminently practical and teachable, The Allyn & Bacon Guide to Writing has set the standard for first-year composition courses in writing, reading, critical thinking, and inquiry.